Pertumbuhan dan Produksi Benih Kacang Panjang (Vigna sinensis L.) pada Pengaturan Jarak Tanam dan Jenis Mulsa - Maulani, Puji Dwi; Prasetyo, Hari (Agropross : National Conference Proceedings of Agriculture, 2023)
Applying the right planting distance and mulch type in field cultivation is one of the efforts made to increase the yield of long bean seeds. This study aims to determine the interaction of planting distance and mulch type on the growth and production of long bean seeds. This research was conducted from September to December 2022 in the rice fields of Puring Village, Patrang District, Jember. The study used a randomized block design (RBD) with 2 factors with 3 replications. The first factor was the planting distance of 30 cm x 30 cm (J1), 30 cm x 40 cm (J2), and 35 cm x 60 cm (J3). The second factor was the type of mulch: no mulch (M0), rice straw mulch (M1), and black and silver mulch (M2). Data were analyzed using Anova and if it showed significantly different, it would be followed by DMRT test at 5% level. The results showed that the interaction between 30 cm x 40 cm spacing (J2) and rice straw mulch (M1) gave the best value for plant length 7 days after planting (13.91 cm), pod length (66.83 cm), number of seeds per pod (16.80 grains), and dry seed weight per pod (2.63 gr).